Validity of High Order Thinking Skills (HOTS) Oriented Student Worksheet (LKPD) on Structure and Function of Plant Tissue Material for Class VIII Junior High School - Ratna Sari Aprilia; Des M; Rahmadhani Fitri; Zulyusri Zulyusri (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Curriculum 2013 push student to have the high order thinking skills (HOTS). But in the SMPN 15 Padang especially in class VIII, there is no available teaching material that can improve students high order thinking skills in the learning process. Therefore, HOTS oriented LKPD has been developed in the structure and function of  plant tissue material. The purpose of this research to know validity of High Order Thinking Skills (HOTS) oriented student worksheet (LKPD) on structure and function of  plant tissue material for class VIII junior high school. This research is part of Plomp model that is development or prototyping phase. Data analyzed through quantitative analysis. The instrument of data collection using validation questionnaires. The product validated by 3 lecturers of biology and a natural science teacher of SMPN 15 Padang. Based on the results of the study obtained the validity of  LKPD 90.96%  with very valid category.